Breed Distribution and Clinical Characteristics of B Cell Chronic Lymphocytic Leukemia in Dogs. (6th January 2016) - Bromberek, J.L.; Rout, E.D.; Agnew, M.R.; Yoshimoto, J.; Morley, P.S.; Avery, A.C.
Abstract : Background: B‐cell chronic lymphocytic leukemia (B‐CLL) is the most common hematopoietic malignancy in humans in the developed world and the primary risk factor is genetic. Dogs also develop B‐CLL, but there is no systematic description of the disease in dogs. Understanding the epidemiology of B‐CLL in dogs may help practitioners recognize the disease and position the dog as a model for future genetic studies. Objectives: To describe B‐CLL presentation in dogs, its clinicopathologic findings, and breed predisposition. Animals: Four hundred and ninety‐one dogs with B‐CLL and 5, 673 control dogs with suspicion of a lymphoproliferative disorder (LPD). Methods: Retrospective cross‐sectional study of dogs for which samples were submitted to the Colorado State University Clinical Immunology Laboratory for immunophenotyping between 2010 and 2014. To assess breed predilection, dogs with B‐CLL were compared to those with suspicion of other LPDs using logistic regression. Results: The median age was 11 years with no sex predilection. Half of the dogs presented with peripheral lymphadenopathy or splenomegaly and 26% had anemia. Eleven small‐breed dogs had significantly increased odds of B‐CLL. In addition, English Bulldogs had an increased risk and a unique presentation: these dogs were diagnosed at a median of 6 years and expressed lower class II MHC and CD25. Conclusions: B‐cell chronic lymphocytic leukemia is overrepresented in small‐breed dogs. Future genetic studies of these breeds may identify genetic risk factors. The unique presentation of English Bulldogs provides evidence of multiple forms of this disease. Additional studies are necessary to determine whether presenting signs are associated with survival.